Notoginsenoside R1 protects against myocardial ischemia/ reperfusion injury in mice via suppressing TAK1-JNK/ p38 signaling - Zeng Jing-jing; Shi Han-qing; Ren Fang-fang; Zhao Xiao-shan; Chen Qiao-ying; Wang Dong-juan; Wu Lian-pin; Chu Mao-ping; Lai Teng-fang; Li Lei (Acta Pharmacologica Sinica, 2023)
Previous studies show that notoginsenoside R1 (NG-R1), a novel saponin isolated from Panax notoginseng, protects kidney, intestine, lung, brain and heart from ischemia-reperfusion injury. In this study we investigated the cardioprotective mechanisms of NG-R1 in myocardial ischemia/reperfusion (MI/R) injury in vivo and in vitro. MI/R injury was induced in mice by occluding the left anterior descending coronary artery for 30 min followed by 4 h reperfusion. The mice were treated with NG-R1 (25 mg/kg, i.p.) every 2 h for 3 times starting 30 min prior to ischemic surgery. We showed that NG-R1 administration significantly decreased the myocardial infarction area, alleviated myocardial cell damage and improved cardiac function in MI/R mice. In murine neonatal cardiomyocytes (CMs) subjected to hypoxia/reoxygenation (H/R) in vitro, pretreatment with NG-R1 (25 μM) significantly inhibited apoptosis. We revealed that NG-R1 suppressed the phosphorylation of transforming growth factor β-activated protein kinase 1 (TAK1), JNK and p38 in vivo and in vitro. Pretreatment with JNK agonist anisomycin or p38 agonist P79350 partially abolished the protective effects of NG-R1 in vivo and in vitro. Knockdown of TAK1 greatly ameliorated H/R-induced apoptosis of CMs, and NG-R1 pretreatment did not provide further protection in TAK1-silenced CMs under H/R injury. Overexpression of TAK1 abolished the anti- apoptotic effect of NG-R1 and diminished the inhibition of NG-R1 on JNK/p38 signaling in MI/R mice as well as in H/R-treated CMs. Collectively, NG-R1 alleviates MI/R injury by suppressing the activity of TAK1, subsequently inhibiting JNK/p38 signaling and attenuating cardiomyocyte apoptosis.